(untitled) (Nepalese Journal of Management Research, 2023)
This study examine the effect of credit performance and interest spread on the profitability of commercial banks in Nepal using panel least squares regression model. The balance panel data of sixteen commercial banks for the year 2013–2021, with 128 observations were used for empirical analysis.The study used non-performing loan ratio (NPLR), credit to deposit ratio (CDR), interest rate spread (IRS), capital adequacy ratio (CAR), customer deposit growth rate (CDGR), and bank size as explanatory variables, and return on asset (ROA) as the dependent variable. The data were collected from the annual report of sample banks, banking and financial statistics, and the bank supervision report published by the Central Bank of Nepal. The study employed a descriptive and causal comparative research design, using Eviews-12 data analysis and modeling software for diagnosis of model, model fit, and analysis. Descriptive statistics, Pearson’s correlation analysis, and multiple regression models were also used. The random effect model was chosen as the fitted model after model diagnosis. The regression model showed that NPLR had a negative and statistically significant impact on ROA, whereas IRS had a positive and statistically significant impact on ROA. However, CDR had a positive but statistically insignificant impact on ROA. Result further showed that capital adequacy ratio, customer deposit growth rate, and bank size had a significant impact on ROA. It can be concluded that the strong credit performance and interest rate spread contribute to increase in bank profitability.